The efficacy of infliximab combined with partial enteral nutrition in the treatment of Crohn’s disease: a cohort study - Huang, Chen; Chen, Chao; Wu, Hao; Yin, Hanyu; Yao, Weixiang; Bai, Susu; Zhuo, Baixue; Wu, Xiaoli (Frontiers in Nutrition, 2025)
Background and aimsThe issue of loss of efficacy with infliximab (IFX) treatment in Crohn’s disease (CD) significantly limits its clinical use. This study aims to investigate the role of therapy combined with partial enteral nutrition (PEN) in maintaining the efficacy of infliximab.MethodsConsecutive CD patients undergoing IFX for induction and maintenance therapy were included, with a follow-up period of at least 54 weeks and endoscopy performed around 54 weeks. Subsequent longitudinal monitoring evaluated improvements in the Crohn’s Disease Activity Index (CDAI) score at 14 weeks and endoscopic remission at 54 weeks.ResultsAmong the 176 included patients, 99 (56%) were in the IFX monotherapy group, and 77 (44%) were in the IFX + PEN group. A significantly higher proportion of patients in the IFX + PEN group achieved clinical response (defined as a CDAI decrease ≥70 points) compared to those in the IFX group at 14 weeks (87.01% vs. 74.75%, p = 0.043), as well as a higher proportion achieving endoscopic remission at 54 weeks (84.42% vs. 65.66%, p = 0.005). Meanwhile, combination therapy with PEN emerged as an independent protective predictor of endoscopic remission at 54 weeks in two multivariate-adjusted models, with ORs of 3.34 and 3.33, respectively (both p < 0.05). Subgroup analysis and interaction test results further supported that all CD patients can benefit from combination therapy with PEN.ConclusionInfliximab treatment combined with partial enteral nutrition is beneficial for both short-term clinical response and long-term endoscopic remission in CD patients.